The Influence of Financial Literacy, Financial Knowledge, And Parental Income On Financial Management Behavior - Desiyanti, Rika; Novita Sari, Julia; Fitria , Reza; Rahmawati, Novia; Yunilma, Yunilma (Management Department, Faculty of Economics and Business, Universitas Bung Hatta, 2025)
This research aims to determine and analyze the effect of financial literacy, financial knowledge, and parental income on financial management behavior in Bung Hatta University students. The variables studied include financial literacy (X1), financial knowledge (X2), and parental income (X3) as independent variables, and financial management behavior (Y) as the dependent variable. The population in this study were Bung Hatta University students, class of 2020- 2022. A sample of 251 respondents using the Proportionate Stratified Random Sampling method. The results of this study indicate that financial literacy has a positive effect on financial management behavior, financial knowledge has a positive effect on financial management behavior and parental income has no effect on financial management behavior.